Economic optimization configuration of energy storage in distribution network considering the attenuation of aging photovoltaic output - HU Haipeng; ZHAO Ping; LI Yan; HOU Qingxing; WANG Guanghui; LI Zhenxing (电力工程技术)
The escalating prevalence of aging distributed photovoltaic (PV) systems has given rise to challenges such as voltage fluctuations and curtailed energy production in large-scale grid-connected systems lacking energy storage. These issues can be effectively mitigated through the strategic deployment of energy storage solutions. In order to enhance the cost-effectiveness of energy storage configuration, an economic optimization method for distribution network energy storage that takes into account the attenuation of aging photovoltaic output is proposed. The impact of aging PV generation decay rate and operational lifespan on actual PV output is thoroughly analyzed, leading to the development of a mathematical relationship between PV output and rated energy storage power and capacity. Building upon this analysis, an optimization model for energy storage configuration is established with a focus on minimizing life cycle costs and reducing voltage deviations at distribution network nodes. This comprehensive approach considers factors such as construction operating costs, network losses, and peak-valley arbitrage income. Finally, particle swarm optimization is employed to solve this complex problem using the IEEE 33-node system. The results demonstrate that the proposed method can achieve significant reductions in both operating cost (33.91%) and life cycle cost (6.01%), thereby validating its economic effectiveness.